Health of Islamic Banks in Indonesia After the Covid-19 Pandemic: Financial Performance Analysis - Fitra Rizal (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Introduction: The Covid-19 pandemic has significantly impacted the global financial sector, including Indonesia. This study aims to analyze the health level of Islamic Commercial Banks after the Covid-19 pandemic in Indonesia using the NPF, ROA, and CAR Ratios from January 2020 to June 2024. Research Methods: The research method used is qualitative with a descriptive approach. Result: The study results show that the average NPF ratio of Islamic Commercial Banks in 2020-2024 was 2.44%, indicating that Islamic Commercial Banks are Healthy. The smaller the NPF, the healthier the bank. The average ROA ratio of Islamic Commercial Banks in 2020-2024 was 1.77%, indicating that Islamic Commercial Banks are in a very healthy condition. The greater the ROA, the healthier the bank. The average CAR ratio of Islamic Commercial Banks 2020-2024 of 24.91% shows that Islamic Commercial Banks are in a very healthy condition. The greater the CAR, the healthier the bank. Conclusion: From the study results above, it can be concluded that the health level of Islamic commercial banks in Indonesia after the Covid 19 pandemic is very well maintained. This confirms that Islamic banks in Indonesia have resilience in facing the economic crisis. This provides confidence for stakeholders to continue investing and participating in the Islamic financial ecosystem.